Analisis Makna Leksikal dan Konotatif Dalam Bahasa Indonesia: Kajian Semantik Terhadap Penggunaan Kata Dalam Pantun Karya Dr. Tenas Effendy - Aura Meriska; Rosenta L Situngkir; Felicia Joice Sitinjak; Rivandi Anju Gurning (Simpati, 2024)
This research aims to analyze the lexical and connotative meanings in Indonesian, with a focus on the use of words in the pantun by Dr. Tenas Effendy. In this research, lexical meaning analysis was carried out using qualitative descriptive methods, with data collection techniques in the form of expansion techniques carried out by expanding the lingual units in question using certain elements. The expansion technique is useful for determining the meaning aspect (semantic aspect) of certain lingual units. The research results show that Dr. Tenas Effendy contains lexical meanings related to concepts such as advice, tradition and life. This lexical meaning is found through analysis of the meaning of the text and the meaning of the pantun context. The meaning of the context in question is in the form of symbolic meaning, namely the meaning contained outside the text and related to the context of the event when the pantun is sung. The conclusion of this research is that Dr. Tenas Effendy has a lexical meaning related to concepts related to life and tradition, as well as a connotative meaning related to symbolism and the context of the event.